2009
DOI: 10.1038/jcbfm.2009.36
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation Extends Brain Tissue at Risk to Vital Peri-Infarct Tissue: A Double Tracer [11C]PK11195- and [18F]FDG-PET Study

Abstract: Focal cerebral ischemia elicits strong inflammatory responses involving activation of resident microglia and recruitment of monocytes/macrophages. These cells express peripheral benzodiazepine receptors (PBRs) and can be visualized by positron emission tomography (PET) using [ 11 C]PK11195 that selectively binds to PBRs. Earlier research suggests that transient ischemia in rats induces increased [11 C]PK11195 binding within the infarct core. In this study, we investigated the expression of PBRs during permanen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
92
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 45 publications
(69 reference statements)
5
92
2
1
Order By: Relevance
“…It was suggesting that 18 F-BCPP-EF could be useful to detect ischemic neuronal damage at the subacute phase 7 days after ischemic insult (Day-7), 7 at which time unexpectedly higher 18 F-fluoro-2-deoxy-Dglucose (FDG) uptake was observed in the damaged area than in the contralateral intact area. 9,10 The FDG-PET is a well-established technique for quantitative imaging of the regional cerebral metabolic rate of glucose (rCMRglc) in living brain, which is based on the assumption that rCMRglc reflects energy metabolism via oxidative phosphorylation. However, the unexpectedly high uptake of 18 F-FDG in ischemia-damaged areas suggested that 18 F-FDG was taken up into not only normal tissues but also inflammatory regions with microglial activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggesting that 18 F-BCPP-EF could be useful to detect ischemic neuronal damage at the subacute phase 7 days after ischemic insult (Day-7), 7 at which time unexpectedly higher 18 F-fluoro-2-deoxy-Dglucose (FDG) uptake was observed in the damaged area than in the contralateral intact area. 9,10 The FDG-PET is a well-established technique for quantitative imaging of the regional cerebral metabolic rate of glucose (rCMRglc) in living brain, which is based on the assumption that rCMRglc reflects energy metabolism via oxidative phosphorylation. However, the unexpectedly high uptake of 18 F-FDG in ischemia-damaged areas suggested that 18 F-FDG was taken up into not only normal tissues but also inflammatory regions with microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the unexpectedly high uptake of 18 F-FDG in ischemia-damaged areas suggested that 18 F-FDG was taken up into not only normal tissues but also inflammatory regions with microglial activation. 9,10 Since recent PET research has indicated that neurodegenerative disorders showed neuroinflammation with microglial activation, 11 PET probes to image MC-I activity would be favorable for more accurate assessment of neurodegenerative damage using PET.…”
Section: Introductionmentioning
confidence: 99%
“…11 C]PK11195 fulfils this requirement by selectively binding to the translocator protein-18 kDa expressed on inflammatory cells, specifically visualizing post-ischemic cellular neuroinflammatory processes [96] . Since [ 11 C]PK11195 is radiolabeled with the isotope 11-C with a half-life of -20 min, sequential PETimaging with [ 18 F]FLT is possible by waiting for -5 half-lives or 100 min between scans.…”
Section: Stem Cell-mediated Regeneration After Focal Cerebral Ischemiamentioning
confidence: 99%
“…A less prominent signal indicating elevated translocator protein 18 kDa expression was observed in the region surrounding the infarct on day 7, which was colocalized with an increased glucose metabolism and accumulated microglias and macrophages. This periinfarct neuroinflammation may contribute to the extension of tissue damage (73).…”
Section: Microglial Activation As An Indicator Of Inflammationmentioning
confidence: 99%